PERAN KOMISI PENGAWAS PERSAINGAN USAHA (KPPU) DALAM MENDORONG IKLIM PERSAINGAN USAHA YANG SEHAT DI SEKTOR PERUNGGASAN - Chandra, Alston; Widiyastuti, Y. Sari Murti (Penerbit Universitas Atma Jaya Yogyakarta, 2017)
ABSTRACTCommission for the supervision of Business Competition was formed on 7th June 2000 based on law no. 5/1999 concerning about Prohibition of Monopolistic Practices and Unfair Business Competition. The main reason of Commission for the supervision of Business Competition is to create a sound and competitive market also prevent monopolistic practices and unfair business competition in the market. Poultry sector is one of many sectors that have been watched by the commission, because there was an indication of monopolistic and unfair business competition in the market. There were at least 12 companies accused for doing monopolistic practices in poultry sector. In this thesis writing, the main discussion is about the role of Commission for the supervision of Business Competition to ensure a sound and equitable competitive condition in poultry sector. With this thesis writing, the writer trying to describe the role of Commission for the supervision of Business Competition in poultry sector whether it is creating a sound and competitive in the market or not. This thesis writing is a normative research which are based on statute approach.Keywords: Commission for the supervision of Business Competition, sound and equitable competitive condition, Poultry Sector.INTISARIKomisi Pengawas Persaingan Usaha (KPPU) dibentuk pada 7 Juni 2000 berdasarkan ketentuan Undang -Undang No.5 Tahun 1999 tentang Larangan Praktek Monopoli dan Persaingan Usaha Tidak Sehat. Alasan utama dibentuknya KPPU adalah untuk menciptakan pasar yang sehat dan kompetitif serta mencegah praktek monopoli dan persaingan usaha tidak sehat. Sektor perunggasan merupakan salah satu daripada banyak sektor yang sedang diawasi oleh KPPU, karena adanya indikasi praktek monopoli dan persaingan usaha tidak sehat di pasar. KPPU menemukan setidaknya ada 12 perusahaan yang terindikasi melakukan praktek monopoli dan persaingan usaha tidak sehat di bidang perunggasan. Topik utama daripada penelitian ini adalah peran KPPU dalam mendorong iklim persaingan usaha yang sehat di sektor perunggasan. Melalui penelitian ini, penulis berusaha untuk menjelaskan peran KPPU dalam melaksanakan tugas pengawasan di sektor perunggasan apakah mendorong untuk terciptanya persaingan usaha yang sehat atau tidak. Metode penelitian yang diguanakan dalam penelitian ini adalah penelitian normative yang mana mendasarkan pada pendekatan Peraturan Perundang-Undangan.Kata Kunci: Komisi Pengawas Persaingan Usaha, Persaingan Usaha yang Sehat, Sektor Perunggasan.